2013
DOI: 10.3390/rs5083803
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Relationships between Net Primary Production and Precipitation in Southern Africa Savannas Using Satellite Observations from 1982 to 2010

Abstract: Abstract:To obtain a better understanding of the variability in net primary production (NPP) in savannas is important for the study of the global carbon cycle and the management of this particular ecosystem. Using satellite and precipitation data sets, we investigated the variations in NPP in southern African savannas from 1982 to 2010, and disentangled the relationships between NPP and precipitation by land cover classes and mean annual precipitation (MAP) gradients. Specifically, we evaluate the utility of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
50
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 55 publications
9
50
0
1
Order By: Relevance
“…Previous studies showed the ability of GIMMS3g to capture productivity dynamics (Wang et al 2014, Zhu & Southworth 2013. Our result of NDVI increasing trends is in agreement with the increase in carbon storage observed for African intact tropical forests ), as well as with the increase in net primary production recorded at a global scale (Nemani et al 2003).…”
Section: Regional Forest Productivity and Climate Variable Trendssupporting
confidence: 79%
“…Previous studies showed the ability of GIMMS3g to capture productivity dynamics (Wang et al 2014, Zhu & Southworth 2013. Our result of NDVI increasing trends is in agreement with the increase in carbon storage observed for African intact tropical forests ), as well as with the increase in net primary production recorded at a global scale (Nemani et al 2003).…”
Section: Regional Forest Productivity and Climate Variable Trendssupporting
confidence: 79%
“…The critical importance of water is well recognized across savanna vegetation types (from open grassland savanna to densely wooded savanna) [11,12], although its role differs across vegetation types and biomes [13]. These studies have also demonstrated that fire regime, soils, herbivory, nutrients and land use also contribute to local patterns of ecosystem structure.…”
Section: Introductionmentioning
confidence: 80%
“…The ANN model showed better performance and was chosen. As for regression variables, we did not use vegetation data as a factor because of the "saturate" effect [71,72], which means it is not a good indicator of precipitation in this area. In addition, many ecology studies usually relate vegetation information (NDVI) to precipitation.…”
Section: Discussionmentioning
confidence: 99%